Effects of absorbed hydrogen on fracture toughness of welded SA516 grade 70 steel - Maslan, Mohamad Haidir (2007)
Effects of absorbed hydrogen on structure and properties of welded A516 Grade-70 steel are investigated. Emphasis is placed on ductility measure of the crack-tip plastic zone under Mode I loading. Specimens are cathodically charged in a cell with dilute sulphuric acid and corrosion inhibitor with uniform charging current density of 20 mA/cm2 and at different exposure time. Results indicate a change from coarse- to fine-grained microstructures in the weld region and heat affected zone (HAZ) of hydrogen-charged specimen. Well-defined ferrite-pearlite bands in the base metal are transformed into coarse-grain structure. Hardness variation along radial distance indicates higher values towards the center of the bar, possibly due to faster diffusion rate but limited solubility of hydrogen. Load-COD responses indicate that slow, stable crack propagation occurred in both base metal and HAZ. The measured provisional fracture toughness, KQ is higher for HAZ than that for the base metal. The toughness values decreases significantly for the initial three hours of hydrogen charging. The tensile fracture region in the immediate fatigue pre-crack tip forms a triangular (rough) zone due to limited constraint to free surface deformation in the thin specimen. Fracture surface of HAZ is dominated by intergranular fracture with localized cleavage facets.